2015
DOI: 10.1038/ncomms7921
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic evolution in diffuse large B-cell lymphomas

Abstract: The contribution of epigenomic alterations to tumour progression and relapse is not well characterized. Here we characterize an association between disease progression and DNA methylation in diffuse large B-cell lymphoma (DLBCL). By profiling genome-wide DNA methylation at single-base pair resolution in thirteen DLBCL diagnosis–relapse sample pairs, we show that DLBCL patients exhibit heterogeneous evolution of tumour methylomes during relapse. We identify differentially methylated regulatory elements and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 49 publications
3
92
0
1
Order By: Relevance
“…5,39,40 Several studies have suggested that both methylases (e.g., EZH2) and demethylases (e.g., KDM6B) coordinate to counterbalance changes in the epigenetic program during development, infection and malignancies. [41][42][43][44][45] This would indicate the importance of KDM6B-derived demethylation in driving proliferation of DLBCL, even in the presence of an activated EZH2-dependent [H3K27(me)3] repressive environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,39,40 Several studies have suggested that both methylases (e.g., EZH2) and demethylases (e.g., KDM6B) coordinate to counterbalance changes in the epigenetic program during development, infection and malignancies. [41][42][43][44][45] This would indicate the importance of KDM6B-derived demethylation in driving proliferation of DLBCL, even in the presence of an activated EZH2-dependent [H3K27(me)3] repressive environment.…”
Section: Discussionmentioning
confidence: 99%
“…2 Histone methylation has been shown to correlate with disease aggressiveness, chemoresistance, and relapse in DLBCL. [4][5][6] Furthermore, expression of several important proteins, such as BCL6, is also regulated by methylation status. 7,8 BCL6 is essential for GCB-cell development, as it is critical to cell proliferation, suppression of the DNA damage response during antibody class switching, and acquisition of somatic hypermutations.…”
Section: Introductionmentioning
confidence: 99%
“…11 Furthermore, it has also been shown that DLBCL pathogenesis is strongly related to epigenetic perturbations and that high epigenomic heterogeneity correlated with a higher relapse rate and poor outcome. 12 These observations open the pathway to specific DNA methyltransferase and histone methyltransferase inhibitors designed to erase aberrant epigenetic programming. 13 Several studies have investigated the genetic landscape of relapsing DLBCL patients and identified TP53, FOXO1, MLL3, CCND3, NFKBIZ, and STAT6 as top candidate genes for therapeutic resistance.…”
Section: Patients With Early Relapsementioning
confidence: 99%
“…They found heterogeneous evolution of DLBCL methylomes and identified a relapse-associated methylation signature enriched in key cellular pathways such as transforming growth factor-β signaling and antiapoptotic pathways. Importantly, the current standard treatment regimen for DLBCL (R-CHOP; rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone) does not seem to be linked to direct effects on DNA methylation or epigenetic modifiers, favoring the conclusion that epigenomic alterations are disease-intrinsic mechanisms of relapse [63].…”
Section: Intertumoral and Intratumoral Heterogeneity Beyond Histopathmentioning
confidence: 99%
“…In an attempt to characterize the epigenome of DLBCL during disease progression, Pan et al [63] performed genomewide DNA methylation profiling in 13 diagnosis-relapse sample pairs at single base pair resolution. They found heterogeneous evolution of DLBCL methylomes and identified a relapse-associated methylation signature enriched in key cellular pathways such as transforming growth factor-β signaling and antiapoptotic pathways.…”
Section: Intertumoral and Intratumoral Heterogeneity Beyond Histopathmentioning
confidence: 99%